GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 10 Apr 2020, 02:44

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# (x – 2)(x + 4) – (x – 3)(x – 1) = 0

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 62696
(x – 2)(x + 4) – (x – 3)(x – 1) = 0  [#permalink]

### Show Tags

Updated on: 10 Jul 2019, 22:48
00:00

Difficulty:

15% (low)

Question Stats:

87% (01:37) correct 13% (02:07) wrong based on 60 sessions

### HideShow timer Statistics

(x – 2)(x + 4) – (x – 3)(x – 1) = 0

(A) –5
(B) –1
(C) 0
(D) 1/2
(E) 11/6

Source: Nova GMAT
Difficulty Level: 550

_________________

Originally posted by Bunuel on 17 Apr 2019, 20:52.
Last edited by SajjadAhmad on 10 Jul 2019, 22:48, edited 1 time in total.
Intern
Joined: 06 Apr 2019
Posts: 7
Re: (x – 2)(x + 4) – (x – 3)(x – 1) = 0  [#permalink]

### Show Tags

18 Apr 2019, 03:32
The approach is simple, just use the FOIL method and then subtract both the sides.

FOIL for (x-2)(x+4) = x^2 + 4x - 2x - 8 = x^2 + 2x - 8
FOIL for (x-3)(x-1) = x^2 - x - 3x + 3 = x^2 - 4x + 3

Substituting them in the equation

(x^2 + 2x - 8) - (x^2 - 4x + 3) = 0
6x - 11 = 0
6x = 11
x = 11 / 6

Hence the answer is option (C)
Intern
Joined: 11 Apr 2019
Posts: 14
Schools: IE MiF "21 (A)
Re: (x – 2)(x + 4) – (x – 3)(x – 1) = 0  [#permalink]

### Show Tags

19 Apr 2019, 04:34
danz1ka19 wrote:
The approach is simple, just use the FOIL method and then subtract both the sides.

FOIL for (x-2)(x+4) = x^2 + 4x - 2x - 8 = x^2 + 2x - 8
FOIL for (x-3)(x-1) = x^2 - x - 3x + 3 = x^2 - 4x + 3

Substituting them in the equation

(x^2 + 2x - 8) - (x^2 - 4x + 3) = 0
6x - 11 = 0
6x = 11
x = 11 / 6

Hence the answer is option (C)

You mean E, right?
Intern
Joined: 06 Apr 2019
Posts: 7
Re: (x – 2)(x + 4) – (x – 3)(x – 1) = 0  [#permalink]

### Show Tags

19 Apr 2019, 11:26
vargamartin1031 wrote:
danz1ka19 wrote:
The approach is simple, just use the FOIL method and then subtract both the sides.

FOIL for (x-2)(x+4) = x^2 + 4x - 2x - 8 = x^2 + 2x - 8
FOIL for (x-3)(x-1) = x^2 - x - 3x + 3 = x^2 - 4x + 3

Substituting them in the equation

(x^2 + 2x - 8) - (x^2 - 4x + 3) = 0
6x - 11 = 0
6x = 11
x = 11 / 6

Hence the answer is option (C)

You mean E, right?

Director
Joined: 27 May 2012
Posts: 972
Re: (x – 2)(x + 4) – (x – 3)(x – 1) = 0  [#permalink]

### Show Tags

23 Apr 2019, 11:49
Bunuel wrote:
(x – 2)(x + 4) – (x – 3)(x – 1) = 0

(A) –5
(B) –1
(C) 0
(D) 1/2
(E) 11/6

Are we supposed to find the value of x, in this question ?
_________________
- Stne
Manager
Joined: 26 Mar 2019
Posts: 115
Re: (x – 2)(x + 4) – (x – 3)(x – 1) = 0  [#permalink]

### Show Tags

02 May 2019, 04:48
stne wrote:
Bunuel wrote:
(x – 2)(x + 4) – (x – 3)(x – 1) = 0

(A) –5
(B) –1
(C) 0
(D) 1/2
(E) 11/6

Are we supposed to find the value of x, in this question ?

Yes. Just simplifying the equation
Intern
Joined: 02 May 2019
Posts: 6
Re: (x – 2)(x + 4) – (x – 3)(x – 1) = 0  [#permalink]

### Show Tags

02 May 2019, 04:56
(x – 2)(x + 4) – (x – 3)(x – 1) = 0
the answer is 5 to this question
Re: (x – 2)(x + 4) – (x – 3)(x – 1) = 0   [#permalink] 02 May 2019, 04:56
Display posts from previous: Sort by